Effects of the Presence of Metastasis on Pain Treatment in Patients with Cancer: A Retrospective Study - Kursun, Yucel Zulfi; Yildiz, Fuat; Kaymaz, Omer; Onal, Selami Ates (Aves, 2014)
Objective: The goal of this study was to investigate the effect of the presence of metastases on pain treatment in patients with cancer-related pain. Methods: Of the 1736 patients who were treated in Firat University, Faculty of Medicine, Department of Anaesthesiology and Reanimation, Algology Section, for cancer-related pain between January 1997 and December 2010, 1467 with complete medical records were evaluated. Patients were grouped as having no metastasis (Group I), a single organ metastasis (Group II), or multiple organ metastasis (Group III). Results: There was no difference between the groups with regard to age. Visual Analog Pain (VAS) scores at admission were higher in Group III compared to the other groups, and significantly higher in Group I than in Group II. Analgesic ladder treatment was given to 85.5% of patients, and 14.5% were treated using additional minimally invasive analgesic procedure (MIVAG) methods. In Group II and Group III, the rates of treatment in Step I and II were lower compared to Group I, while the rates of treatment in Step III were higher. Implementation of MIVAG was higher in Group III than in the other groups, and higher in Group II than in Group I. Conclusion: The presence of metastases causes more severe pain, which becomes more difficult to treat, and increases the analgesia step and the consumption of opioids in patients with cancer-related pain.
Keywords: Cancer; pain; metastasis; analgesics